2009
DOI: 10.1007/s00267-008-9260-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Postfire Vegetation Dynamics of Mediterranean Shrub Species Based on Terrestrial and NDVI Data

Abstract: The present study offers an analysis of regeneration patterns and diversity dynamics after a wildfire, which occurred in 1993 and affected about 7000 ha in southern Spain. The aim of the work was to analyze the rule in the succession of shrub species after fire, relating it to the changes registered in the Normalized Difference Vegetation Index (NDVI). Fractional vegetation cover was recorded from permanent plots in 2000 and 2005. NDVI data related to each time were obtained from Landsat images. Both data sets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In other burned areas, highly flammable tussock grasses (some of which are alien) can replace locally dominating woody species, resulting in increasing frequencies of very large and intense fires (Grigulis et al, 2005;Vilà et al, 2001). Several studies have confirmed that the recovery rate of scrub cover after fire was quite rapid, often exceeding the pre-fire biomass amount (Hernandez-Clemente et al, 2009;Roder et al, 2008;Viedma et al, 1997). Simulation models such as FATELAND and BROLLA have shown an increase in shrublands as a response to increased fire frequency, creating a state of successional stagnation which may enhance the positive shrub-fire feedback (Pausas, 1999;Pausas and Lloret, 2007) (Fig.…”
Section: Fire Frequency Is Higher In Previously Burned Areasmentioning
confidence: 97%
“…In other burned areas, highly flammable tussock grasses (some of which are alien) can replace locally dominating woody species, resulting in increasing frequencies of very large and intense fires (Grigulis et al, 2005;Vilà et al, 2001). Several studies have confirmed that the recovery rate of scrub cover after fire was quite rapid, often exceeding the pre-fire biomass amount (Hernandez-Clemente et al, 2009;Roder et al, 2008;Viedma et al, 1997). Simulation models such as FATELAND and BROLLA have shown an increase in shrublands as a response to increased fire frequency, creating a state of successional stagnation which may enhance the positive shrub-fire feedback (Pausas, 1999;Pausas and Lloret, 2007) (Fig.…”
Section: Fire Frequency Is Higher In Previously Burned Areasmentioning
confidence: 97%
“…Usually, these index transforms are based on thorough field calibration. Only few studies incorporated a substantial number of field plots to calibrate and validate the VI approach (Shaw et al 1998;Bisson et al 2008;Clemente et al 2009;Jacobson 2010;Segah et al 2010;van Leeuwen et al 2010;Vila and Barbosa 2010;Veraverbeke et al 2011bHernandez-Clemente et al 2009). Figure 1 presents an example of the relationship between the NDVI and field estimates of vegetative cover which was used to model post-fire vegetation cover in the burned area.…”
Section: Vismentioning
confidence: 99%
“…Previous research has noted the possibility of full regeneration of forest type vegetation to pre-fire conditions in a time period of thirteen years following a major wild-land fire [40]. Changes in species composition and initial increases in species abundance have been observed in the first stages of forest recovery [51], on temporal scale of one to three years, followed by lower levels in subsequent years [41,52]. However, increased levels of wild-land fire severity have been shown to decrease overall species abundance [53].…”
Section: Satellite Derived Ndvimentioning
confidence: 99%
“…A significantly larger and darker post-fire burn scar was observed for areas affected by the BLC (Figure 3), which indicates greater vegetation damage and potential landscape change, and may be attributed to the prior abundance of woody vegetation, typically observed in this mixed conifer area [22,34]. Vegetation types and post-fire vegetation regrowth dynamics are believed to have been contributing factors leading to less noticeable BHC burn scar and increased NDVI recovery (Figures 3(e) and (h)) [22,40,41]. Results of the NDVI post-fire image comparisons between complexes, however, may have been influenced by differences in NDVI recovery time, because in efforts aimed at consistency, collection of post-fire NDVI images for both complexes were derived from a further dated singular post-fire image, then transformed into NDVI grey-scale images.…”
Section: Ndvi Grayscale Imagerymentioning
confidence: 99%
See 1 more Smart Citation